2009
DOI: 10.1086/597222
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone‐Mediated Effects on Fitness‐Related Phenotypic Traits and Fitness

Abstract: The physiological and behavioral mechanisms underlying life-history trade-offs are a continued source of debate. Testosterone (T) is one physiological factor proposed to mediate the trade-off between reproduction and survival. We use phenotypic engineering and multiple laboratory and field fitness-related phenotypic traits to test the effects of elevated T between two bank vole Myodes glareolus groups: dominant and subordinate males. Males with naturally high T levels showed higher social status (laboratory do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
109
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 90 publications
9
109
3
Order By: Relevance
“…Therefore reduced male survival due to increased malemale aggression likely did not affect males at the ages in our study. However, testosterone levels increase with the onset of sexual maturity in male pinnipeds (Lydersen and Kovacs 2005) and reduced immunity associated with testosterone production (Mills et al 2009) compounded with stress from high pubertal growth may increase mortality risk for males from 4-8 yrs. Other sexspecific physiological factors such as reduced immunity and ability to utilize fat during food shortages for males compared to females (Widdowson 1976, Hill et al 1986, Chin et al 2005 may be detrimental to males of all ages.…”
Section: Sex Effectsmentioning
confidence: 99%
“…Therefore reduced male survival due to increased malemale aggression likely did not affect males at the ages in our study. However, testosterone levels increase with the onset of sexual maturity in male pinnipeds (Lydersen and Kovacs 2005) and reduced immunity associated with testosterone production (Mills et al 2009) compounded with stress from high pubertal growth may increase mortality risk for males from 4-8 yrs. Other sexspecific physiological factors such as reduced immunity and ability to utilize fat during food shortages for males compared to females (Widdowson 1976, Hill et al 1986, Chin et al 2005 may be detrimental to males of all ages.…”
Section: Sex Effectsmentioning
confidence: 99%
“…In support of this notion, experimental increases in testosterone, within normal physiological limits, suppress immune function and increase parasite loads in several species (24,25). In addition, some studies in wild vertebrates have found that highranking males have high testosterone and/or glucocorticoids and poor health (18,21,26,27). Hence, in addition to the social stress associated with low rank, differences in reproductive effort also may cause status-related differences in health.…”
mentioning
confidence: 94%
“…Indeed, several studies of vertebrates have documented a major life history tradeoff between male reproductive effort and health (18)(19)(20). This tradeoff is thought to be mediated by testosterone and sometimes by glucocorticoids, which help direct energetic resources toward reproduction and away from tasks associated with long-term survival, such as immune function (15,17,(21)(22)(23). In support of this notion, experimental increases in testosterone, within normal physiological limits, suppress immune function and increase parasite loads in several species (24,25).…”
mentioning
confidence: 97%
“…Hormones are also expected to be intimately related to fitness, and they often mechanistically underlie life-history trade-offs among fitness components such as survival and reproduction Stearns 1992;Sinervo and Svensson 1998;Zera and Harshman 2001;Ricklefs and Wikelski 2002;AdkinsRegan 2005;Breuner et al 2008;Lessells 2008;Mills et al 2008Mills et al , 2009Bonier et al 2009a). Despite the expected relationship between hormones and fitness, we have little information about how selection acts on individual variation in hormone levels and hormone-mediated traits in the wild (Kingsolver et al 2001;Adkins-Regan 2005).…”
Section: Introductionmentioning
confidence: 99%